ANALISA AYAT-AYAT ISRÂF PERSPEKTIF PSIKOLOGIS BERBASIS AL-QUR'AN SEBAGAI PENANGGULANGAN PERILAKU BERLEBIHAN - Nurbaiti Nurbaiti; Made Saihu (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
This paper aims to explain the prevention of excessive behavior in humans obtained from the analysis of the isrâf verses with a psychological approach. Through library research methods and psychological approaches, this study shows that the verses of the Qur'an that discuss excessive behavior include the word isrâf with various variations. Some of the variations such as; verbs with fi'il madhi, verbs with fi'il nahyi, verbs with harfu jazmi (lam), ismu fail musrif in mufrad and plural forms. The various uses of the word isrâf in these verses give rise to various interpretations when carried out with a psychological approach. The psychological approach is used in this study, because the authors consider it a relevant and appropriate approach to discussing human behavior, such as excessive behavior. The results of various interpretations with this psychological approach then become a type of excessive behavior in humans, which is then found several relevant countermeasures for excessive behavior in today's human lifestyle.